Design and energy analysis of novel hydraulic regenerative potential energy systems. (15th June 2022) - Tan, Lisha; He, Xiangyu; Xiao, Guangxin; Jiang, Mengjun; Yuan, Yulin
Abstract: Potential energy regeneration is an important hydraulic energy-saving technology in construction machinery. However, the existing hydraulic regenerative potential energy system (HRPES) is still limited by its large size, high cost, circuit interference, and so on. To solve the above problems, this paper intends to study novel HRPES by optimizing the hydraulic circuits and hydraulic components. First, we design four new HRPESs according to the working characteristics of energy recovery and energy reuse of construction equipment. Based on the load data of the 1.7-ton experimental excavator and the HRPES simulation model, the working characteristics of HRPES in the process of multicycle energy regeneration are studied. Finally, in addition to the conventional energy-saving efficiency, this paper proposes the recovery efficiency, reuse efficiency and regeneration efficiency to comprehensively analyse the energy efficiency characteristics of the four HRPESs. The results show that the energy-saving efficiencies of the four HRPESs are 16.02%, 22.84%, 21.95%, and 27.15% compared with traditional No-HRPES, and the regeneration efficiencies are 54.43%, 57.76%, 53.55%, and 57.97%, respectively. These results have an important reference for optimizing the structure of existing HRPES. Graphical abstract: Potential energy regeneration is an important hydraulic energy-saving technology in construction machinery. However, the existing hydraulic regenerative potential energy system (HRPES) is still limited by its large size, high cost, circuit interference, and so on. To solve the above problems, this paper intends to study novel HPRES by optimizing the hydraulic circuits and hydraulic components. Image 1 Highlights: Novel hydraulic regenerative potential energy systems (HRPESs) are discussed. The hydraulic schematic of HRPESs is designed, and the energy flow is analysed. Simulation models of HRPESs based on an experimental excavator are established. An energy analysis of HRPESs is conducted for energy efficiency and energy loss.